Labour Management "Trust Relations" as Reflected in Collective Agreement Clauses - Fricke, John G. (Relations industrielles / Industrial Relations, 1991)
Joint labor-management committees are a well established institution in industrial relations in Canada. A critical evaluation was conducted of the labor-management communication clauses in the total population of collective agreements (1,093) filed with Alberta Labor as of May 31, 1987. Provisions for joint labor-management committees or meetings were contained in 428 of these agreements. Of these, 384 specified a decision format (advisory or executive) and were separated into those representing low trust, moderate trust, and high trust. It was found that the largest number of committees in the low trust provisions were of the general purpose type and advisory in nature. For the moderate trust and high trust provisions, the number of general purpose committees was 35.5% and 25.6%, respectively. Special purpose committees seemed to be favored in the manufacturing and services sectors at all levels of trust.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Clauses; Collective bargaining; Committees; Employees; Labor Unions; Labor contracts; Labor relations; Manyindustries; Participatory management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical data